A Confessional Account of an Ethnography About Knowledge Work1 - Schultze, Ulrike (MIS Quarterly, 2000)
Information systems research has traditionally focused on information as an object that serves as input to decision making. Such a perspective attends mainly to the use of information. Increasingly, however, organizations are concerned about the production of information. This paper focuses on the work of producing informational objects, an activity central to knowledge work. Based on data collected during an eight-month ethnographic study of three groups of knowledge workers—computer system administrators, competitive intelligence analysts, and librarians—I explore the informing practices they relied upon. These are identified as ex-pressing, monitoring, and translating. Common to these informing practices is the knowledge workers’ endeavor to balance subjectivity and objectivity, where subjectivity is a necessary part of doing value adding work and objectivity promises workers authority and a sense of security. Recognizing that researchers are knowledge workers too, I draw on my own experiences as an ethnographic researcher to identify parallels between my informing practices and those of the knowledge workers I studied. These parallels are intended to challenge the taken-for-granted assumptions underlying scientific practice. I adopt a confessional genre of representation for this purpose.